Stand and Site Characteristics of Kabesak (Acacia leucophloea) in Timor Island, East Nusa Tenggara, Indonesia - Arnold C. Hendrik; Cecep Kusmana; Muhdin (Jurnal Penelitian Kehutanan Wallacea, 2019)
Kabesak (Acacia leucophloea) is a particular plant species and recognized to have important benefits tothe local people of Timor Island. The people of Timor Island use kabesak leaves as animal feed in the dry season and kabesak wood is used as building materials and furniture. The purpose of this study wasto determine the stand and site characteristics ofkabesak in the western region of Timor, Indonesia. The means of density, frequency, dominance, and importance value index were analyzed. The results showed kabesak stand structure in secondary forest land, grassland, and shrubs, as well as garden showed the J-inverted shaped, which implies that natural regeneration was a proper continuation. Kabesak had significant associations with a few plants’ species, both negative and positive types. The result of regression analysis of the principal components showedthat the contribution of edaphic factor influencesthe population density of kabesak.Silt fraction and phosphorus content were found tohave the highest positive effect on the density, while sand fraction and sodium content were found to havethe highestnegative effectsof kabesak. A test for altitude with Tukey test (α = 0.05) reveals that kabesak from 0-300 m a.s.l., 300-600 m. asl., 600-900 m a.s.l. werenot different from each other, while altitude >900 m a.s.l. was significantly different from the other groups.